The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/nu15183875
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on Healthy Eating Impact the Home Food Environment: A Qualitative Exploration of Perceptions of Indigenous Food Gatekeepers in Urban Fiji

Shazna M. Buksh,
Phillipa Hay,
John B. F. de Wit

Abstract: The home food environment (HFE) can have important direct and indirect impacts on dietary practices. Nutrient transitions in the HFE of Pacific Island countries (PICs) are key contributors of the high rates of adult and childhood overweight and obesity in the region. Pacifica mothers are important sociocultural agents who play critical roles in their HFE through setting eating-appropriateness standards and mitigating the impacts of food availability and accessibility on the HFE. This study used an interpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…These findings are echoed and expanded on by other research, creating a detailed narrative about the dietary preferences and challenges faced by Indigenous populations in various contexts. For example, Buksh et al's study on urban Indigenous Fijian mothers' percep-tions similarly emphasized the importance of traditional cuisine and food preparation methods in regard to healthy eating [30]. This study underscored the complex, multifaceted nature of healthy eating within Indigenous communities, where traditional foods are not only preferred for their freshness and natural qualities but also act as crucial elements in preserving and transmitting culture [30].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These findings are echoed and expanded on by other research, creating a detailed narrative about the dietary preferences and challenges faced by Indigenous populations in various contexts. For example, Buksh et al's study on urban Indigenous Fijian mothers' percep-tions similarly emphasized the importance of traditional cuisine and food preparation methods in regard to healthy eating [30]. This study underscored the complex, multifaceted nature of healthy eating within Indigenous communities, where traditional foods are not only preferred for their freshness and natural qualities but also act as crucial elements in preserving and transmitting culture [30].…”
Section: Discussionmentioning
confidence: 85%
“…For example, Buksh et al's study on urban Indigenous Fijian mothers' perceptions similarly emphasized the importance of traditional cuisine and food preparation methods in regard to healthy eating [30]. This study underscored the complex, multifaceted nature of healthy eating within Indigenous communities, where traditional foods are not only preferred for their freshness and natural qualities but also act as crucial elements in preserving and transmitting culture [30]. Furthermore, the emphasis on maintaining a Our study reveals that urban Indigenous populations perceive healthy eating as a blend of mainstream nutritional advice-which emphasizes nutrient-rich foods, minimizes unhealthy ingredients, focuses on home-cooked meals, and adheres to dietary guidelines-and a deep respect for traditional foods.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of low fruit and vegetable consumption despite access, and of high BMI despite reportedly low unhealthy food consumption, also may suggest a lack of diet and nutrition awareness in PIC populations. That is, Pacific Islanders may perceive fruits and vegetables as healthy but have poor understanding of the quantity that have to be consumed [44]. Buksh et al [33] found that Fijians talked about vegetables as being of low social value and not indicative of a good meal, and that consumption of calorie-dense foods was high because they were viewed as more satiating.…”
Section: Discussionmentioning
confidence: 99%
“…Buksh et al [33] found that Fijians talked about vegetables as being of low social value and not indicative of a good meal, and that consumption of calorie-dense foods was high because they were viewed as more satiating. Similarly, Pacifica mothers described switching from SSBs to equally unhealthy fruit concentrates, as the latter were perceived as being healthier [44]. Additionally, PIC populations may not be aware that the levels of sugar and salt in single servings of SSBs and ultra-processed snacks are beyond daily limits, or what a standard serving is compared to the size of the purchased item (e.g., size of SSB bottle or box of snacks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation